Characterization of the nearly complete mitochondrial genome of a Chinese endemic stonefly species, Caroperla siveci (Plecoptera: Perlidae). Issue 1 (2nd January 2019) - Cao, Jinjun; Wang, Ying; Li, Ni; Li, Weihai; Chen, Xiling
Abstract: The stonefly Caroperla Siveci, an unusual and endemic new species, only distributed to the Wuyi Mountain, Fujian Province, China. Here, we sequenced and determined the complete mitochondrial (mt) genome of C. Siveci representing the genus Caroperla for the first time. The total genome size is 15, 353 bp in length. The nucleotide composition is A (35.2%), T (32.3%), C (20.5%), and G (11.9%). Mostly PCGs use the typical start codon ATN, except ND1, ND2, and ND5, which start with TTG, GTG, and GTG. The COI, COIII, and ND5 genes stopped with incomplete stop codon T and the rest use stop codon TAN. C. siveci was recovered as a sister-group to the clade ((Acroneuria + Dinocras) + (Togoperla + Kamimuria)). This mitogenome will assist a variety of biodiversity researches, especially in taxonomy and phylogeny of stoneflies.